In vitro studies on antioxidants and free radical scavenging activities in the extracts of Loranthus longiflorus desr. bark samples obtained from two host trees - Chandrakasan, L; Neelamegam, R (Journal of Phytology, 2011)
Antioxidant compounds and their free radical scavenging (FRS) activities in various solvent extracts of Loranthus longiflorus bark samples collected from Casuarina equisetifolia and Ficus religiosa host trees were assessed. The results obtained confirm the presence of total flavonoids, total phenols and total tannins in all extracts at different proportions. Among the extracts tested, ethyl acetate extract shows maximum total phenols (301.25mg/g and 307.27mg/g) and total tannins (11.46mg/g and 204.83mg/g),while chloroform extract favours more amount of flavonoids (18.92mg/g and 26.13mg/g) in Loranthus bark samples collected from the host Casuarina and Ficus, respectively. Among the extracts of Loranthus bark samples, collected from Casuarina and Ficus, ethanol extract shows maximum scavenging activity on DPPH (4681.8% and 4890.6% at 1500µg), on Hydroxyl (49.37% and 55.58% at 250 µg), ethyl acetate (49.79%) and water extract (48.28%) on Nitric oxide (at 250µg) and ethanol (33.71%) chloroform (34.85%) on Superoxide (at 250 µg), respectively, as compared to other extracts. All the FRS activities, tested, were concentration dependent. The inhibitory concentration (IC50) was determined in ethanol extracts as 5.70µg/ml and 5.32µg/ml for DPPH-FRS activity; as 34.34µg/ml and 38.35 µg/ml for HO-FRS activity, as 108.93µg/ml and 104.32µg/ml for SO-FRS activity and ethyl acetate extract as 188.5µg/ml and 116.1µg/ml for NO-FRS activity of Loranthus bark samples collected from Casuarina and Ficus, respectively, than other extracts, tested. The ferric reducing antioxidant power of Loranthus bark samples, from Casuarina and Ficus hosts, was maximum in ethanol extract (4053.53 and 4199.03mMol Fe (II)/mg extract, respectively) than other extracts tested. These results indicate that the host trees, on which the hemiparasite infested, influence the variations in antioxidant constituents and free radical scavenging activities of L. longiflorus bark extracts.